1996
DOI: 10.4319/lo.1996.41.2.0333
|View full text |Cite
|
Sign up to set email alerts
|

Parent lithology, surface–groundwater exchange, and nitrate retention in headwater streams

Abstract: We address the ecological ramifications of variation in hydrologic interaction between streams and alluvial aquifers in catchments with alluvium derived from parent materials of contrasting geologic composition. We present a conceptual model in which solute retention in streams results from hydrologic retention (increased water residence time resulting from surface-groundwater exchange), biological nutrient cycling, and chemical processes. Solute injection experiments were done in study catchments comprised of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
371
4
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 401 publications
(406 citation statements)
references
References 34 publications
30
371
4
1
Order By: Relevance
“…Hall et al (2002) also addressed the effect of surface water pools on TS estimates (in contrast to true hyporheic exchange); our results showed a similar effect where leaf litter reduced hyporheic exchange, but also created some local pooling of water (based on visual observations). Other studies relating TS and nutrient uptake have been equivocal (Hall et al 2002;Roberts et al 2007), showing negative , neutral (Martí et al 1997;Butturini and Sabater 1999;Simon et al 2005) and positive effects (Valett et al 1996;Mulholland et al 1997;Argerich et al 2008). Our results suggest that the effect of TS on NH 4…”
Section: How Important Was Ts On Ammonium Uptake?supporting
confidence: 68%
“…Hall et al (2002) also addressed the effect of surface water pools on TS estimates (in contrast to true hyporheic exchange); our results showed a similar effect where leaf litter reduced hyporheic exchange, but also created some local pooling of water (based on visual observations). Other studies relating TS and nutrient uptake have been equivocal (Hall et al 2002;Roberts et al 2007), showing negative , neutral (Martí et al 1997;Butturini and Sabater 1999;Simon et al 2005) and positive effects (Valett et al 1996;Mulholland et al 1997;Argerich et al 2008). Our results suggest that the effect of TS on NH 4…”
Section: How Important Was Ts On Ammonium Uptake?supporting
confidence: 68%
“…Peterson et al (2001) reported that more than 50% of inorganic nitrogen inputs were assimilated in headwater streams, a value confirmed by Kroger et al (2007) in Mississippi agricultural drainage ditches. Streams with low flow volumes and discharge rates generally have greater capacity for pollutant attenuation (Vallett et al, 1996). In vegetated headwater streams, where flow velocity and thus discharge rate is reduced, substantial amounts of nitrate attenuation have been documented (Cooper & Cooke, 1984).…”
Section: Stream Hydrology Managementmentioning
confidence: 99%
“…Small-scale investigations are essential to identify processes, yet results are usually too variable from site to site to reliably quantify cumulative effects. On the other hand, stream-tracer studies (50-500 m) cannot always reliably isolate or distinguish hyporheic-zone processes from other processes , A number of previous investigators characterized reactive solute transport by injecting reactive constituents into both the stream and subsurface [Bencala et al, 1984; Triska et al, 1993;Valett et al, 1996]. That strategy is an excellent means to investigate processes; however, because of the substantially elevated concentrations of the reactive constituent, the results might not represent natural reaction rates.…”
Section: Investigating the Cumulative Effects Of Hyporheic Processesmentioning
confidence: 99%